The Age-Related Perfusion Pattern Measured With Arterial Spin Labeling MRI in Healthy Subjects - Zhang, Nan; Gordon, Marc L.; Ma, Yilong; Chi, Bradley; Gomar, Jesus J.; Peng, Shichun; Kingsley, Peter B.; Eidelberg, David; Goldberg, Terry E. (Frontiers in Aging Neuroscience, 2018)
Aim: To analyze age-related cerebral blood flow (CBF) using arterial spin labeling (ASL) MRI in healthy subjects with multivariate principal component analysis (PCA). Methods: 50 healthy subjects (mean age 45.8 ± 18.5 years, range 21-85) had 3D structural MRI and pseudo-continuous ASL MRI at resting state. The relationship between CBF and age was examined with voxel-based univariate analysis using multiple regression and two-sample t-test (median age 41.8 years as a cut-off). An age-related CBF pattern was identified using multivariate PCA. Results: Age correlated negatively with CBF especially anteriorly and in cerebellum. After adjusting by global value, CBF was relatively decreased with aging in certain regions and relatively increased in others. The age-related CBF pattern showed relative reductions in frontal and parietal areas and cerebellum, and covarying increases in temporal and occipital areas. Subject scores of this pattern correlated negatively with age (R2 = 0.588; P < 0.001) and discriminated between the older and younger subgroups (P < 0.001). Conclusion: A distinct age-related CBF pattern can be identified with multivariate PCA using ASL MRI.